Design and Motion Analysis of an Automatic Retractable Manipulator for a Vehicle-mounted Wheelchair - Cui Jiahui; Li Lin; Liang Dong; Qin Chengxin (Jixie chuandong)
A five degrees of freedom manipulator for automatic retractable vehicle-mounted wheelchairs is proposed. Firstly, the mathematical model of the manipulator is established according to the D-H method, and the forward and inverse kinematics analysis is carried out. When the inverse kinematics analysis is carried out, the analytical method and the back propagation (BP) neural network are used to solve the problem respectively. Secondly, the quintic polynomial interpolation method is used to plan the joint space trajectory of the manipulator, so as to realize the smooth and impact-free movement of the manipulator. Then, the workspace of the manipulator is analyzed based on the Monte Carlo method, and the point nephogram of the workspace for the end positioning of the manipulator is obtained. Finally, virtual simulation experiment is carried out for specific vehicle-mounted application scenarios. The simulation results show that the design of the manipulator is reasonable, the movement is flexible, and it meets the application requirements, which will provide a theoretical basis for the development and application of the prototype.